Analysis of Laws Governing Terms in Patent Licensing Contracts for Commercialisation (Kanun: Jurnal Undang-undang Malaysia, 2022)
A licence contract is a form of contract entered into in writing, based on terms agreed upon between the contracting parties relating to patent licensing. It is one of the ways of exploiting intellectual property made for the purpose of commercializing patented inventions. Previous studies have found that misuse of patent rights by contracting parties can occur through the terms included in the licence contract. Therefore, this article aims to identify the law and analyse its provisions governing the terms in the licence contract. To achieve this objective, this article uses the library research for the analysis of relevant legal documents such as Acts, decided cases, books, and journals. The findings show that there are legal provisions in Malaysia that govern the terms included in patent licensing contracts. However, improvements need to be made to the legal provisions for the purpose of facilitating the implementation of patent licensing contracts.Keywords: Intellectual property, terms, patent, license contract, commercialisation, MalaysiaFull text: PDF